2022
DOI: 10.1161/jaha.122.024849
|View full text |Cite
|
Sign up to set email alerts
|

Guideline‐Recommended Time Less Than 90 Minutes From ECG to Primary Percutaneous Coronary Intervention for ST‐Segment–Elevation Myocardial Infarction Is Associated with Major Survival Benefits, Especially in Octogenarians: A Contemporary Report in 11 226 Patients from NORIC

Abstract: Background Using contemporary data from NORIC (Norwegian Registry of Invasive Cardiology) we investigated the predictive value of patient age and time from ECG diagnosis to sheath insertion (ECG‐2‐sheath) in primary percutaneous coronary intervention for ST‐segment–elevation myocardial infarction (STEMI). Methods and Results Data from 11 226 patients collected from all centers offering 24/7/365 primary percutaneous coronary intervention s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
3
3
0
Order By: Relevance
“…Of note, ST-segment deviations are essential in standardized guidelines for the diagnosis of myocardial ischemia, the assessment of ischemia severity, and the prognosis evaluation ( 19 ). Consistent with a previous report ( 20 ), we demonstrated that age is a risk factor for MACEs prediction in patients with STEMI. Previous studies have demonstrated that renal dysfunction is an important risk factor after acute MI ( 21 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of note, ST-segment deviations are essential in standardized guidelines for the diagnosis of myocardial ischemia, the assessment of ischemia severity, and the prognosis evaluation ( 19 ). Consistent with a previous report ( 20 ), we demonstrated that age is a risk factor for MACEs prediction in patients with STEMI. Previous studies have demonstrated that renal dysfunction is an important risk factor after acute MI ( 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…ST-segment deviations caused by loss of the cell membrane in the injured myocardium (18) had the greatest contribution in our model. Of note, ST-segment deviations are essential in standardized guidelines for the diagnosis of myocardial ischemia, the assessment of ischemia severity, and the prognosis evaluation (19). Consistent with a previous report (20), we demonstrated that age is a risk factor for MACEs prediction in patients with STEMI.…”
Section: Selected Variables Mirror Critical Pathophysiological Proces...supporting
confidence: 91%
“…This confirmed that meeting time targets of <90 minutes recommended in the guidelines was associated with a large survival benefit, especially among the octogenarians. 18 The current findings as well as those reported in literature 10,18 indicated better survival through invasive strategy even in older patients. 5 The current study has limitations as it was a single-centre, observational, retrospective study, and STEMI and NSTEMI patients were not separately compared because of the small sample size.…”
Section: Discussionsupporting
confidence: 82%
“…Larsen et al 18 recently conducted a study comprising 11,226 patients who underwent primary PCI for STEMI. Of them, 1,400 patients were over 80 years old.…”
Section: Discussionmentioning
confidence: 99%
“…While organizational measures can enhance the system delay, patient delay is influenced by multiple factors. System delay serves as a prognostic indicator for mortality in STEMI patients undergoing primary PCI (1)(2)(3). So, one of the key factors in effectively managing patients with STEMI is minimizing the time from hospital arrival to balloon inflation, commonly referred to as door-to-balloon time (DBT).…”
Section: Introductionmentioning
confidence: 99%